ANALISIS KONSEPSI PESERTA DIDIK DALAM MENYELESAIKAN SOAL MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL MENGGUNAKAN TEKNIKCERTAINTY OF RESPONSE INDEX (CRI) DI KELAS VIII SMPN 4 PAYAKUMBUH - Reni Aprilianti (Jurnal Edukasi dan Penelitian Matematika, 2019)
The concept is a basic thing that must be understood by students in learning mathematics, but in fact there are many students who do not understand the concept and experience misconceptions. This study aims to determine the conceptions of students and describe the reason why the students do not understand the concepts and face misconceptions. This type of research is descriptive research with research subjects, that is the students of class VIII.4 Payakumbuh SMP 4 who are grouped in three types. These are the students who understand the concepts, they are who facing misconceptions, and they are who do not understand the concept in solving questions equipped with CRI. The research instruments use by the researcher are test in question form and interview. The data analysis technique uses descriptive qualitative. The results showthat there are students who understand the concept, and do not understand the concept, but there is nostudentwho identified facing the misconceptions. The causes of the students do know the concept are a) talking becomes a habit to the students when the teacher explains the material, b) the less of motivation of the students to discuss when they are given times to to an exercise. They would prefer to copy what their friends have done, c) lack of motivation of students in learning mathematics. Keywords – CRI, concept, misconceptions